HUBUNGAN PENGGUNAAN LENSA KONTAK DENGAN KEJADIAN SINDROM MATA KERING PADA MAHASISWA FK UHT SURABAYA ANGKATAN 2019 DAN 2020 - Callista Vivien Earlyanti (Surabaya Biomedical Journal, 2024)
Abstract Introduction : The use of contact lenses can cause dry eye syndrome due to impaired meibomian gland function. Impaired meibomian gland function causes the tear film to evaporate quickly. Contact lenses decrease the production of the tear film reflex due to decreased sensitivity of the ocular surface. The tear film becomes unstable due to friction between the contact lens and the surface of the eye. Decreased tear film production and increased evaporation due to contact lens wear increase the occurrence of dry eye syndrome. Case Report : Based on this study, 26 out of 41 respondents who filled out the OSDI questionnaire experienced dry eye syndrome. Then, of the 41 people who underwent the Schirmer test, 23 of them had dry eye syndrome. The research results obtained a significance value of more than 0.005 where H1 was rejected and H0 was accepted. Discussion : Dry eyes due to soft contact lenses are influenced by many factors, namely factors from the respondents themselves such as age, gender, general health, eye health and use of systemic drugs. Lens material and lens replacement schedule, lens disinfection systems, use of lens drops, additional treatments such as additional supplements, topical medications, punctal plugs, ergonomic factors and environmental factors. Keywords : contact lenses, dry eye syndrome, OSDI questionnaire, Schirmer test.